The Plymouth Rock of the American West: Remembering, Forgetting, and Becoming American in Utah - Patterson, Sara M. (Material religion, 2015)
This paper examines how Utah's 1947 This Is The Place Monument functioned in two contradictory ways: First, it confirmed the Mormon narrative of their entry into the Salt Lake Valley as a mythic narrative about a chosen people entering into their promised land. Second, it reinforced Mormonism as one among many traditions participating in the civil religion of Utah and the American West. In its exploration of these contradictory impulses, the paper examines the intersections of historical memory and the creation of sacred space.